Kerangka Manajemen Pendidikan Qur'ani Berdasarkan QS. Al-Baqarah Ayat 30–37 - Muhammad Syaifullah; Mohammad Yusuf (Education Achievement: Journal of Science and Research, 2026)
Educational management has become a strategic element in improving the quality, effectiveness, and sustainability of educational institutions. Most educational management theories have been developed from organizational and administrative perspectives, while studies reconstructing educational management directly from the narrative structure of the Qur'an remain limited. This study aims to reconstruct a Qur'anic Educational Management Framework based on Surah Al-Baqarah verses 30–37. The research employed a qualitative library research approach using thematic Qur'anic interpretation (tafsīr mawḍū‘ī), content analysis, comparative analysis, and conceptual synthesis. Primary data were derived from the Qur'an and classical as well as contemporary tafsir literature, while secondary data consisted of educational management literature and relevant scholarly publications. The findings reveal that Surah Al-Baqarah verses 30–37 describe a systematic educational process comprising six interconnected domains: Educational Vision and Mission Setting, Competency Development and Assessment, Leadership Legitimization and Organizational Culture, Value- and Rule-Based Educational Governance, Accountability and Consequence Enforcement, and Reflective Learning and Continuous Improvement. These six domains form an integrated and cyclical framework of educational management rooted in Qur'anic values, in which each domain serves as the foundation for the subsequent stage and collectively supports continuous organizational improvement. This study contributes to the discourse on Islamic educational management by proposing a conceptual framework reconstructed directly from the narrative structure of the Qur'an rather than by adapting existing management theories. The framework provides an alternative epistemological foundation for developing educational institutions that are ethical, trustworthy, adaptive, and committed to sustainable quality improvement.